KESIAPAN PERGURUAN TINGGI DI INDONESIA DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (ASEAN ECONOMIC COMMUNITY/AEC) - Sulbahri Madjir (JURNAL KOMPETITIF, 2015)
ABSTRACTÃ‚Â Readiness Higher Education in Indonesia in Facing the ASEAN Economic Community (ASEAN Economic Community /AEC) is the structuring of education policy, reform the system and the administration or management of education and the arrangement of academic and student development strategy with regard to the development factors of physical needs and the needs of the motives and knowledge and skills of graduate students to become qualified and productive at work.Keywords : Higher Education Readiness and the ASEAN Economic Community.